2015
DOI: 10.1016/j.bbrc.2015.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a dipeptidyl peptidase IV inhibitor from aronia juice

Abstract: Aronia berries have many potential effects on health, including an antioxidant effect, effect for antimutagenesis, hepatoprotection and cardioprotection, an antidiabetic effect and inhibition of cancer cell proliferation. Previous human studies have shown that aronia juice may be useful for treatment of obesity disorders. In this study, we found that aronia juice has an inhibitory effect against dipeptidyl peptidase IV (DPP IV) (EC 3.4.14.5). DPP IV is a peptidase that cleaves the N-terminal region of incretin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…The anthocyanins cyanidin 3, 5-diglucoside isolated from the juice of aronia berries (Kozuka et al, 2015) and cyanidin 3-glucoside found in blackberry-blueberry wine blend (Fan et al 2013) have both been reported to have DPP-IV inhibitory activity (IC50 = 5.5 µM and 0.42 µM, respectively). Phytochemicals found in extracts from Greek oregano, rosemary, marjoram and Mexican oregano were also recently found to be able to inhibit the DPP-IV enzyme in a study by Bower, Hernandez, Berhow, & de Mejia (2015).…”
Section: Other Food Constituents With Dpp-iv Inhibitory Activitymentioning
confidence: 99%
“…The anthocyanins cyanidin 3, 5-diglucoside isolated from the juice of aronia berries (Kozuka et al, 2015) and cyanidin 3-glucoside found in blackberry-blueberry wine blend (Fan et al 2013) have both been reported to have DPP-IV inhibitory activity (IC50 = 5.5 µM and 0.42 µM, respectively). Phytochemicals found in extracts from Greek oregano, rosemary, marjoram and Mexican oregano were also recently found to be able to inhibit the DPP-IV enzyme in a study by Bower, Hernandez, Berhow, & de Mejia (2015).…”
Section: Other Food Constituents With Dpp-iv Inhibitory Activitymentioning
confidence: 99%
“…Chlorogenic acid was found to be the most potent inhibitor of pancreatic α-amylase [16]. Other studies postulated that the antidiabetic effect of black chokeberry juice may be due to the cyaniding 3,5-diglucoside inhibition of DPP IV (dipeptidyl peptidase IV) [112]. It seems that in humans, black chokeberry juice can be an excellent natural alternative therapeutic strategy for the treatment of metabolic syndrome disorders, the dose varying from 100 ml to 300 ml per day, for at least 3 months [16].…”
Section: Anti-diabetic Effectmentioning
confidence: 99%
“…Kozuka et al [83] tested the juice of aronia berries (Aronia sp., Rosaceae) as DPP-4 inhibitors. Enzymatic activity was determined by fluorometry (excitation 380 nm and emission 440 nm), and DPP-4 inhibition was performed using L-proline 4-methyl-coumaryl-7-amide (Pro-MCA) as the substrate in Tris-HCl (pH 9.0).…”
Section: Potentiality Of Medicinal Plants As Incretin Modulatorsmentioning
confidence: 99%